The lake house : a novel - Patterson, James (New York : Little, Brown and Company, 2003)
The memorable story begun in When the Wind Blows continues in this thrilling novel, and it's one that really soars! Frannie O'Neil, a Colorado veterinarian, knows a terrible secret that will change the history of the world. Kit Harrison, an FBI agent under suspension has seen things that no one in his right mind would believe. A twelve-year-old girl named Max and five other incredible children have powers we can only dream of. These children can fly. And the only place they will be safe is the Lake House. Or so they believe...
Keywords: Human experimentation in medicine -- Fiction; Suspense fiction